Economic crisis and forest cover change in Cameroon: the role of migration, crop diversification, and gender division labor - Sunderlin, William D.; Pokam, J. (2002)
Dating from 1986 when a devastating economic crisis began, the rate of deforestation has increased significantly in the humid forest zone of Cameroon. Research was conducted in 1997-98 to know how the crisis has affected socioeconomic conditions, and how these changes have in turn affected forest cover. A survey of 4,078 households in 38 villages tested three hypotheses concerning the effects of the crisis on migration, cropping patterns, and the gender division of labor. Among the key findings are that: (1) on average, population in the villages has grown considerably in response to inmigration, slowed rural to urban migration, and recent net “return” migration; (2) there has been a massive turn to production of food crops; (3) new food crop production tended to be at the expense of forest cover because many farmers retained their cocoa and coffee plots; (4) men are now highly involved in the production of food crops; and (5) the amount of forest clearing in 1996 was largely a function of increased food crop production and distance from the capital city. Policy efforts aimed at controlling inappropriate deforestation must recognize that macroeconomic conditions can have an important role in influencing migration, food crop choices, and gender division of labor, which in turn influence forest cover change.